Aspek Melawan Hukum Pidana Terhadap Perbuatan Penyalahgunaan Wewenang Dalam Penyaluran Bantuan Sosial Di Masa PSBB - Christian Victor Samuel Marzuki; John Dirk Pasalbessy; Jetty Martje Patty (Faculty of Law, Universitas Pattimura, 2021)
Introduction: There is a policy that the government is proposing in order to cope with the COVID-19 social disaster, which is followed by actions that affect it caused by actions that are not in accordance with the provisions contained in the legislation and are carried out by officials who have the authority to do otherwise and in accordance with the provisions which exists.Purposes of the Research: Reviewing and discussing acts of abuse of authority and unlawful elements of the distribution of social assistance are classified as criminal acts.Methods of the Research: This research is a normative legal research or legal research literature (Library research). Normative legal research examines laws that are conceptualized as applicable norms or rules. The applicable legal norms are in the form of written positive legal norms formed by statutory institutions (Basic Law, codification, laws, government regulations, and so on).Results of the Research: Abuse of authority in the distribution of social assistance is a form of crime, in the social assistance distribution program held by the government through the Ministry of Social Affairs of the Republic of Indonesia, it is proven to have abused authority. This can be proven by the case of unlawful elements of the abuse of authority over social assistance during the PSBB period by Juliari Batubara who is a former Minister of Social Affairs. The unlawful element in the act of abusing the authority of social assistance during the PSBB period is an act that is considered as an element of enriching oneself which is part of an unlawful act as contained in Article 2 and Article 3 of Law no. 31 of 1999 concerning the Eradication of Criminal Acts of Corruption, one of which is committing acts of enriching oneself or another person, or an entity and indirectly harming state finances and/or the state economy.